Strength building methods efficiency rating experiment - Belegov, A. N.; Sivokhin, I. P.; Skotnikov, V. F.; Fedorov, A. I.; Tapsir, M.; Kalashnikov, A. P.; Komarov, O. Y. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to provide experimental data to assess practical benefits of the strength building techniques with application of variable weights customizable to the trainees` individual natural traits. Subject to the study were 36 young people of 18-22 years of age not engaged in professional sports. The study data and findings may be applied to design efficient individualized strength building models with a special focus on the key muscle groups employed in the practices.